Efektivitas Manajemen Risiko Pembiayaan di BNI Syariah Cabang Surabaya dalam Pengendalian Pembiayaan Bermasalah - Ahsan, Muhamad; Al-Azhar, Muhammad Farid (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
This study aims to examine the role of internal audit as a function of supervision of the effectiveness of risk management with the competence of account officers as an intervening variable in BNI Syariah Surabaya Branch. The method used in this study is quantitative associative with a saturated sample of 34 people consisting of internal audit employees, account officers, financing units, and risk management. Data were analyzed using Partial Least Square (smartPLS 3.0). The results show that the role of internal audit is not directly influenced to the effectiveness of financial risk management, internal audit has a positive effect on the competency of account officers, and account officer becomes an intervening variable on the effectiveness of risk management. Practical implications, BNI Syariah Surabaya must maintain and strengthen the role of internal audit and account officers to reduce financing risks.